Bridging Gaps: Strategies for Competitiveness and Survival of IAIN Langsa Islamic Education Graduates in the Eastern Coast of Aceh - Sabri, Hatta; Z, Syamsiah; Endri Santi, Nani; Efendi, Rizal; Khairiah, Khairiah (Jurnal Penelitian Pendidikan Islam, 2025)
This study examined the competitiveness and survival strategies of Islamic Education (PAI) graduates from IAIN Langsa in the Aceh Timur region, including East Aceh Regency, Kota Langsa, and Aceh Tamiang. Higher education institutions, particularly Islamic Studies programs, are responsible for preparing graduates to meet the demands of an increasingly dynamic and globalized job market. This research aimed to explore the challenges faced by PAI alumni in adapting to globalization, digitalization, and evolving market expectations. Using a mixed-methods explanatory sequential design, quantitative data were collected via online surveys from 165 alumni graduating in 2021, 2022, and 2023. The survey measured indicators such as job waiting periods, relevance of employment to academic background, income levels, and workplace challenges. Qualitative data were subsequently obtained through in-depth interviews with 10 purposively selected alumni. Quantitative findings were analyzed using descriptive statistics, while qualitative data underwent thematic analysis, supported by method triangulation and a focus group discussion (FGD) with experts and alumni. Results indicated significant gaps in technical skills, including IT proficiency, foreign language competency, and public speaking. While most alumni pursued careers in education, others entered diverse fields, employing adaptive survival strategies influenced by socio-cultural expectations in Aceh. These findings contribute to curriculum refinement and institutional strategies to enhance graduate competitiveness and employability.